PENGARUH FASILITAS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA ASN MELALUI KEPUASAN KERJA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL SITUBONDO - Fikri, Moh Ali; Arief, Mohammad Yahya; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2023)
Human resource management is the management and utilization of resources available in individual. This research used work facilities and work discipline variables as the independent variables and job satisfaction and performance as the dependent variables. The purpose of this research was to analyze and examine the influence of work facilities and work discipline on state civil apparatus performance through Job satisfaction at Civil Registry Service Office of Situbondo. The population in this study was 33 state civil apparatus and the sample used was 33 state civil apparatus at Civil Registry Service Office of Situbondo. The analysis and testing method in this research applied Partial Least Square - Structural Equation Modeling (PLS- SEM). The results of direct influence hypothesis test using Smart PLS 3.0 application reveale that work facilites have a negative but not significant influence on job satisfaction, work discipline has a significant positive influence on job satisfaction, work facilities have a negative but not significant influence on performance, work discipline has a significant positive influence on performance , job satisfaction has a significant positive influence on performance. The results of indirect influence hypothesis test showed that work facilities variable has no significant negative influence on performance through job satisfaction, work discipline has a significant positive influence on performance through job satisfaction.